-2(-y-5)-7(4y-7)=y+5+3y

Simple and best practice solution for -2(-y-5)-7(4y-7)=y+5+3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-y-5)-7(4y-7)=y+5+3y equation:


Simplifying
-2(-1y + -5) + -7(4y + -7) = y + 5 + 3y

Reorder the terms:
-2(-5 + -1y) + -7(4y + -7) = y + 5 + 3y
(-5 * -2 + -1y * -2) + -7(4y + -7) = y + 5 + 3y
(10 + 2y) + -7(4y + -7) = y + 5 + 3y

Reorder the terms:
10 + 2y + -7(-7 + 4y) = y + 5 + 3y
10 + 2y + (-7 * -7 + 4y * -7) = y + 5 + 3y
10 + 2y + (49 + -28y) = y + 5 + 3y

Reorder the terms:
10 + 49 + 2y + -28y = y + 5 + 3y

Combine like terms: 10 + 49 = 59
59 + 2y + -28y = y + 5 + 3y

Combine like terms: 2y + -28y = -26y
59 + -26y = y + 5 + 3y

Reorder the terms:
59 + -26y = 5 + y + 3y

Combine like terms: y + 3y = 4y
59 + -26y = 5 + 4y

Solving
59 + -26y = 5 + 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
59 + -26y + -4y = 5 + 4y + -4y

Combine like terms: -26y + -4y = -30y
59 + -30y = 5 + 4y + -4y

Combine like terms: 4y + -4y = 0
59 + -30y = 5 + 0
59 + -30y = 5

Add '-59' to each side of the equation.
59 + -59 + -30y = 5 + -59

Combine like terms: 59 + -59 = 0
0 + -30y = 5 + -59
-30y = 5 + -59

Combine like terms: 5 + -59 = -54
-30y = -54

Divide each side by '-30'.
y = 1.8

Simplifying
y = 1.8

See similar equations:

| -5y+20=-5y | | =325*-7 | | x+3-4=3(5+4) | | 21=3/8n | | 4(x-2)+3=25 | | y=4(-3)+8 | | 9x-3x(x-5)=6x+3 | | 13/20/1/6 | | (8x^3-28x^2)-(10x+35)= | | 1.9(7.766x-6.71)=66.9302 | | 5-11=33 | | -5(y-4)=-3y+8y | | (-15/36)*x^2 | | 5/6(y)-3/4(y)=-3 | | m-m+5m-4m=13 | | 6x+2-4(x+5)=18 | | 3+4*5x=67 | | 3v^2+11v+6=0 | | 11+5n=-2(-n+5)+6(2n+3) | | -2+6(-6m-5)=4 | | 4c-4c+4c=20 | | (2a+b)+(4b+5)= | | 4+7n=9n | | 8(8a+8)=-64 | | 3[2-(2t+5)]-1=2(5-t) | | 42=-4k | | 6·1-6/1 | | -7(n-4)=-28 | | 3b-3b+b-b+b=9 | | 14w-5w+5=14 | | 6x+18=10+8x | | 0.25x+5=5+0.25x |

Equations solver categories